2020
DOI: 10.1021/acs.jafc.9b06679
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Soil Degradation Rate of 5-Substituted Sulfonylurea Herbicides as Novel AHAS Inhibitors

Abstract: Chlorsulfuron has been applied in wheat fields as a recognized herbicide worldwide, yet it was officially banned in China since 2014 for its soil persistence problem. On the basis of our previous research that 5-dimethylamino distinctively accelerated degradation rate in soils, a modified amino moiety (Ia-c) and monosubstituted amino group (Id-e) were introduced onto the fifth position of the benzene ring in sulfonylurea structures, as well as heterocyclic amino substituents (If-g) to seek a suitable soil degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…The previous studies reported that the primary target of chlorsulfuron and other sulphonylurea herbicides is acetolactate synthase, the enzyme specifically involved in branched-chain amino acids biosynthesis (Zhou et al 2007, Orcaray et al 2010. But, there was no significant decrease of branched-chain amino acids under chlorsulfuron stress in maize.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The previous studies reported that the primary target of chlorsulfuron and other sulphonylurea herbicides is acetolactate synthase, the enzyme specifically involved in branched-chain amino acids biosynthesis (Zhou et al 2007, Orcaray et al 2010. But, there was no significant decrease of branched-chain amino acids under chlorsulfuron stress in maize.…”
Section: Discussionmentioning
confidence: 95%
“…(2-chloro-N- [(4-methoxy-6-methyl-1,3, 5-triazine-2-yl) aminocarbonyl]-benzene-sulfonamide) is a selective, systemic post-emergence herbicide. It was the first sulfonylurea herbicide approved in the United States (Zhou et al 2020), and globally, it was one of the most commonly used herbicides of its type for removing broadleaf weeds and other weedy annuals in wheat and barley fields. According to existing reports, the primary target of chlorsulfuron and other sulfonylurea herbicides is acetolacetate synthase (ALS), the enzyme specific to branched-chained amino acid biosynthesis (Fan 2003).…”
Section: Chlorsulfuronmentioning
confidence: 99%
“…4 Its inhibition interrupts the catalytic cycle and protein synthesis in the meristem by blocking cell division, resulting in the inhibition of growth and subsequent death of plants. 5 The antifungal property provides sulfonylureas the potential of being used as antifungal additives in the silage process. Forage is a vegetal material used for animal feed and, during the silage process, it may be affected by fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous herbicides, with approximately 20 modes of actions (MOA), have been discovered and marketed from the 1950s to the 1990s . Examples of herbicidal inhibiting actions include protoporphyrinogen oxidase (PPO), , acetohydroxyacid synthase (AHAS), , acetyl-CoA carboxylase (ACCase), 4-hydroxyphenylpyruvatedioxygenase (HPPD), and many others.…”
Section: Introductionmentioning
confidence: 99%